PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA MINIMARKET LULUMART DI KOTA SAMARINDA - irfan afria shandy (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
This study aims to determine the effect of Marketing Mix variable on purchasing decision at Lulumart Minimarket located in Samarida. Variable used in this study consisted of the independent variable, namely the product (X1), price (X2), place (X3), promotion (X4), people (X5), physical evidence (X6), and process (X7) and the dependent variable is the purchase decision (Y1). Data collection techniques is questionnaire and interview methods. For testing the instrument using validity test, reliability, and the classic assumption test. For data analysis techniques using multiple linear regression method with the F test and t test. The results show that the seven variables simultaneously have a significant effect on customer purchasing decision on Lulumart Minimarket (Y1). The main suggestion for Lulumart Minimarket in Samarinda is research related to consumer behavior, especially regarding the effect of marketing mix on purchasing decision if it can be used as a reference in making management decision for the progress of the retail business.